SCHOOL MANAGEMENT AUTOMATION: ANALYZING THE IMPACT OF MANAGEMENT INFORMATION SYSTEMS ON THE EFFECTIVENESS OF THE LEARNING PROCESS - Antono Damayanto; Alim Hardiansyah; Adhe Risky Mayasari (International Journal of Teaching and Learning, 2025)
School management automation through Management Information Systems (MIS) is the application of technology to automate, integrate and optimise administrative and academic processes within the school environment. The research method used in this study was literature research. The results show that cost challenges are often the biggest barrier, with budget restrictions making it difficult for some educational institutions to support the initial investment and ongoing operational costs of SIM. Solutions include finding alternative funding models, partnering with technology companies, and adopting cloud-based solutions to reduce infrastructure costs. Regarding user resistance, it was found that effective training programmes and awareness campaigns on the benefits of SIM can minimise the discomfort of adapting to new technology. Finally, in the area of data security, the findings emphasise the importance of security audits, user training, and compliance with data protection regulations to maintain the integrity and privacy of institutional data. This research demonstrates that although challenges exist, with the right strategies, SIM implementation can optimise school management functions and enrich the learning process.